Moving a House with Preservation in Mind - Paravalos, Peter (Rowman & Littlefield Publishers, 2006)
House moving has recently been pushed to the forefront of preservation efforts as an alternative to demolition. When the choice becomes to either move a historically significant building away from its original physical and cultural landscape, or see history torn down and buried away in our ever-growing landfills, relocation can be the preferred option. Aggressive residential and business developments have forced preservationists, historical commissions, and concerned citizens to act by moving historic homes in an effort to save them from destruction. What is involved in moving a house? Where does one begin? Most importantly, what will it cost? Moving a House with Preservation in Mind can be used as a reference book by anyone contemplating a house move, whether historic or non-historic, as they decide whether to undertake such a complex project. The book examines the process of moving a house step by step, from the planning stage through cost analysis, funding availability, moving options, and the physical move. A detailed case study illustrates the importance of house moving in preservation, and the final chapter provides briefer examples of several house moves across the U.S. and the various obstacles each encountered. Written by a structural engineer specializing in building relocation projects with a background and active role in historic preservation, Moving a House with Preservation in Mind uses clear text and insightful photographs to make technical issues easily accessible. Peter Paravalos explores a variety of move types, underscoring the important dos and don'ts that will help to make your project a success.